Keyword: Algorithm - Gillespie, Tarleton (Digital Keywords: A Vocabulary of Information Society and Culture, 2016)
For "algorithm," the technical specialists, the social scientists, and the broader public are using the word in different ways. For software engineers, algorithms are often quite simple things; for the broader public they name something unattainably complex. For social scientists, algorithm lures us away from the technical meaning, offering an inscrutable artifact that nevertheless has some elusive and explanatory power . We find ourselves more ready to proclaim the impact of algorithms than to say what they are. This is not to say that critique requires a settled, singular meaning, or that technical meanings necessarily trump others. But we should be cognizant of the multiple meanings of algorithm as well as the discursive work the term performs.
(Ben Peters, ed.)